Dehydroepiandrosterone and Its Derivatives: Potentially Novel Anti-Proliferative and Chemopreventive Agents - Matsuzaki, Y.; Honda, A (Current Pharmaceutical Design, 2006)
Dehydroepiandrosterone (DHEA) is the most abundant adrenal androgenic steroid in young adult humans. The physiological functions of DHEA in preventing human carcinogenesis are still controversial, but a lot of reports have shown that pharmacological doses of DHEA show chemopreventive and anti-proliferative effects on tumors in rodents. Although a therapeutic dose of DHEA has been reported to promote hepatocarcinogenesis in rats due to peroxisomal proliferation, it remains unclear whether DHEA is a peroxisome proliferator in human liver. The chemopreventive and anti-proliferative effects of DHEA are not explained by a single mechanism, and at least four mechanisms seem to contribute to these effects: 1) depletion of NADPH and ribose-5-phosphate due to the inhibition of glucose-6-phosphate dehydrogenase activity, 2) suppression of cholesterol biosynthetic pathway by inhibition of HMG-CoA reductase, 3) interference with cell proliferation signaling pathways, and 4) suppression of nitric oxide generation through down-regulation of nitric oxide synthase II. In addition to studies of the mechanisms underlying the anti-neoplastic effects, searches for more potent and less androgenic DHEA derivatives are ongoing. A small amount of DHEA is endogenously metabolized to 7-oxygenated DHEA, and this may represent a metabolic pathway to more potent steroid hormones. Androsterone, epiandrosterone and etiocholanolone have been considered to be merely inactive end products of DHEA, but may in fact be physiological effectors in their own right. In addition, DHEA analogs such as 3β-methyl-5-androsten-17-one, 16α-fluoro-5-androsten-17-one and 16α-fluoro- 5α-androstan-17-one have been synthesized and shown to be more effective inhibitors of tumor growth, compared with DHEA itself. However, to design potent and safe DHEA derivatives, identification of the DHEA receptor and clarification of the mechanisms of DHEA action are required.
Keywords: Dehydroepiandrosterone